Pengaruh Penambahan Lindi dan Mikroorganisme Lokal (MOL) Rebung Terhadap Proses Pengomposan Sampah Organik Pasar Tradisional - , Disnanda Utamifa Jannahdita; Mirwan, Mohamad (Jurnal Serambi Engineering, 2025)
Composting is one way of managing organic waste from traditional markets. However, this process takes a long time, so bioactivators are needed to speed up decomposition. Leachate and bamboo shoot MOL (local microorganisms) can serve as bioactivators as they contain the necessary microorganisms and nutrients. This study examines the effect of adding leachate and bamboo shoot MOL to compost organic waste from traditional markets. The composting process used vegetable waste, coconut pulp and sawdust as raw materials, with 1-litre doses of each bioactivator variation. The results showed that the bamboo shoot MOL and the leachate-MOL combination treatments reached standard levels of C, N, P, K and the C/N ratio faster than the control treatment and the leachate-only treatment. The C/N ratios were as follows: control (19.91); leachate (18.15); bamboo shoot MOL (15.41); and leachate-MOL combination (17.73). All of these met the compost quality standard based on SNI 19-7030-2004. Physical changes in the compost occurred faster in the bamboo shoot MOL treatment (day 15) and the combination treatment (day 18) than in the leachate-only treatment (day 21) and the control treatment (day 24). Based on these results, bamboo shoot MOL was proven to be the most effective treatment for accelerating the composting process and improving the quality of the final compost.